Creativity, Collaboration and Development in Jeremy Thurlow's Ouija for Peter Sheppard Skærved. Issue 1 (2nd January 2016) - Clarke, Eric; Doffman, Mark; Timmers, Renee
ABSTRACT: This article documents and analyses a creative collaboration between the composer Jeremy Thurlow and the violinist Peter Sheppard Skærved in the production of Ouija, a work for solo violin and laptop computer. The article situates the account of this creative process within recent literature on distributed and collaborative creativity, and focuses on three aspects of the project: verbal interaction between the two musicians, analysed in terms of 'creative-talk' and 'face-talk', and the relationship between immediate and more contextual concerns ('inside/outside the room'); a quantitative analysis of changes in the musical material, focusing on timing; and a qualitative analysis of the role of the violinist's embodied and instrumental engagement with the music. The article discusses the findings in relation to forwards-orientated (process) and backwards-orientated (product) conceptions of creativity, the operation of different social components in creative collaboration and the relationship between craft, history and embodiment.